Experience operating a trolleybus equipped with traction batteries nLTO - Hurtová, Ivana; Sejkorová, Marie; Verner, Jan (Kaunas University of Technology, 2017)
This paper presents the new lithium-titan (nLTO) battery. A technology using nano crystals as energy storage for the public transport means. The town’s public transit company “Dopravní společnost Zlín-Otrokovice (DSZO)” has acquired a new trolleybus Škoda 26Tr. The vehicle is equipped with traction batteries (nLTO) and was put into trial operation in 2016. DZSO is the first company in the Czech Republic which uses a trolleybus with nLTO. This paper compares a trial operation of ŠKODA 24Tr with an auxiliary diesel engine and a new trolleybus with nLTO. Furthermore, the article compares the economic analysis of operation including evaluation of costs per one km.
Praktické zkušenosti s provozem trolejbusu využívající trakčních baterií nLTO
Keywords: electric mobility; electric bus; nano lithium-titanate battery; nLTO; elektromobilita; elektrický autobus; nano lithium-titanátová baterie; nLTO